Adaptasi Kultural dan Data Normatif Pemeriksaan Olfaktori pada Populasi Lansia Indonesia - Martin, Juvenius; Chandra, Kenly; Vebriana, Gennesia; Putra, Aditya; Kristian, Kevin; Handajani, Yvonne Suzy; Turana, Yuda (PERHATI-KL, 2025)
Background: The olfactory sense plays a vital role in well-being and cognitive health, particularly in the older adults. Olfactory dysfunction is linked to neurodegenerative diseases, and geriatric syndromes like frailty. Existing cognitive tests are education-biased, limiting their applicability. Cultural adaptation of olfactory tests enhances diagnostic accuracy, necessitating region-specific normative data for Indonesia. Purpose: To establish normative olfactory scores for Indonesia’s older adult population using a culturally adapted odor identification test. Method: A descriptive study was conducted on 205 healthy participants aged 60 and above, in Jakarta. Eight culturally familiar odors were used in a forced-choice identification test. Normative data were generated based on percentiles, with the 10th percentile serving as the cut off for hyposmia. Data were analyzed using Statistical Package for the Social Sciences (SPSS). Result: Olfactory function was found to decline with age. Hyposmia thresholds were determined: individuals aged 60-64 years were considered hyposmic if they identified fewer than five odors, while those aged 80+ were hyposmic if they identified fewer than two odors. No significant differences were found between education levels, as both groups shared the same hyposmia thresholds. Conclusion: The study provided normative olfactory data specific to the Indonesia’s older adult population. These results supported the use of culturally adapted tests in clinical practice to detect olfactory dysfunction, which might indicate early cognitive decline. Further research should include longitudinal studies to capture changes over time.